2021
DOI: 10.3389/fimmu.2021.649475
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Gene Expression Analysis of Mtb-Infected DC Highlights the Rapamycin-Driven Modulation of Regulatory Cytokines via the mTOR/GSK-3β Axis

Abstract: In human primary dendritic cells (DC) rapamycin—an autophagy inducer and protein synthesis inhibitor—overcomes the autophagy block induced by Mycobacterium tuberculosis (Mtb) and promotes a Th1 response via IL-12 secretion. Here, the immunostimulatory activity of rapamycin in Mtb-infected DC was further investigated by analyzing both transcriptome and translatome gene profiles. Hundreds of differentially expressed genes (DEGs) were identified by transcriptome and translatome analyses of Mtb-infected DC, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Studies have reported on the complex immune regulatory networks perturbed by Mtb infection to increase its survival. Mtb infection up-regulates mTOR activity and upon treatment with rapamycin, IL-12 production and Th1 response goes high to clear the pathogen [ 58 ] . The former results exhibited active perturbation of HIF-1α and CPT1a in NCoR1 depleted DCs promoted a Th1 response via reduction of IL-10 to IL-12 cytokine balance.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported on the complex immune regulatory networks perturbed by Mtb infection to increase its survival. Mtb infection up-regulates mTOR activity and upon treatment with rapamycin, IL-12 production and Th1 response goes high to clear the pathogen [ 58 ] . The former results exhibited active perturbation of HIF-1α and CPT1a in NCoR1 depleted DCs promoted a Th1 response via reduction of IL-10 to IL-12 cytokine balance.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that Mtb tyrosine phosphatase PtpA led to dephosphorylation of GSK-3α ( 7 ). In human primary dendritic cells (DC), Mtb infection modulated pro- and anti-inflammatory cytokine production through mTOR/GSK-3β axis ( 8 ). However, the exact efficacy and molecular mechanisms as how GSK-3α/β interacts with Mtb infection in Mφs remain undefined.…”
Section: Introductionmentioning
confidence: 99%
“…The number of samples in non-infected (NI), live MTB-infected, and heat-inactivated (HI) MTB-infected group were 17, respectively, at multiple time points in hours (h), 2 h, 18 h, 48 h, and 72 h. DCs were infected with MTB for time series at a multiplicity of infection (MOI) of 1 or with HI MTB at MOI of 5. GSE163531 [ 12 ] dataset was obtained from GPL20265 platform and 8 DC samples from blood were treated with or without virulent MTB H37Rv (ATCC 27,294) at MOI of 1 bacterium/cell for 16 h. DCs were generated by culturing CD14 + monocytes with 50 ng/ml granulocyte-macrophage colony-stimulating factor (GM-CSF) and 1000 U/ml IL-4. Detailed information about these datasets were listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%